Spectral Element Modeling of Acoustic to Seismic Coupling Over Topography. Issue 1 (15th January 2022) - Bishop, Jordan W.; Fee, David; Modrak, Ryan; Tape, Carl; Kim, Keehoon
Abstract: Acoustic waves in the atmosphere are commonly recorded on seismometers as they couple into the ground. These signals, here called ground coupled airwaves, are not commonly considered in numerical modeling of infrasound propagation, which often assumes a rigid unmeshed boundary. Starting from an analytically‐tractable spherical wave model, we analyze how the coupling of an acoustic wave into a planar elastic halfspace changes over a wide range of scenarios. We use energy admittance to quantify acoustic to seismic coupling over both a planar elastic halfspace and meshed topography. Our spectral element and analytic calculations have different maxima as a function of incidence angle, with very high admittance values for near‐vertical incidence (maximum ≈78%). Energy admittance calculations at shallow incidence angles are much smaller (less than 1%). In simulations over the complex topography of Sakurajima Volcano, we attribute the variable spatial pattern of energy admittance to changes in earth parameters between each model. The observed pressure difference over the simulated 15 km region appears to be < 2 % < 2% . While this value is relatively small, the cumulative addition over 100s of km and multiple acoustic bounce points may be significant. Acoustic to seismic coupling along the propagation path may bias long distance yield estimates, particularly when infrasound propagates over regions with steep topography or particularly slow seismic velocities, such as alluvial planes. Plain Language Summary: When numerically modeling how low‐frequency sound waves travel over the Earth's surface, it is usually assumed that the Earth does not react to the sound waves. This approximation can make the numerical modeling faster and easier, but it ignores the fact the we often observe that sound waves convert into seismic waves when they encounter the Earth's surface. Here we estimate how much energy is moved from the sound wave into the seismic wave in order to better understand potential inaccuracies in previous modeling efforts. We find that the change is small, but now we have an estimated number. This kind of estimate is important when trying to analyze how a complex source like a volcanic eruption or a chemical explosion releases seismic and infrasound waves, which can in turn help inform future estimates of explosion size and other important characteristics. Key Points: Fully‐coupled simulations with SPECFEM3D show medium‐dependent acoustic to seismic coupling patterns over realistic, complex topography Coupling into the earth results in a small but often notable reduction in the peak amplitude of observed infrasound waves (<2%) Acoustic to seismic coupling along the propagation path may be an additional attenuation mechanism for long range infrasound propagation